A Call for Help?: How Public School Principals' Subjective Report of Institutional Weakness Relates to Disciplinary Incidents. (1st October 2020) - Martinez, Julia A.
ABSTRACT: Disciplinary incidents at U.S. public middle- and high-schools are a public policy concern. Although businesses popularly give credence to leaders' subjective intelligence, principals' reports of their schools' strengths and weaknesses are questioned. To determine whether principals' reports carry legitimacy as indicators of student offenses, the current study utilized a nationally representative survey of principals who reported on their sense of the institution and the number of disciplinary incidents in the past year ( N = 1, 872; replication cohort, N = 1, 833). Findings showed that the more institutional shortcomings a principal endorsed, the higher total number of incidents occurred, even after controlling for institutional strength and several indicators of school crime. These findings have policy and intervention implications for improving student outcomes, and so would be of interest to funding agencies, school administrators, teachers, and parents.